Revision of the Ambrysus pulchellus Montandon species complex (Heteroptera: Nepomorpha: Naucoridae) - Reynoso-Velasco, Daniel; Sites, Robert W. (Zootaxa, 2018)
The Ambrysus pulchellus Montandon species complex is revised and includes A. buenoi Usinger, A. californicus Montandon, A. pulchellus Montandon, and A. vanduzeei Usinger. The unifying features among species in this complex are related to the morphology of the male phallosoma and the medial lobes of abdominal tergum VIII. The species in this complex are diagnosed and a key for identification is presented. The subspecies A. pulchellus nitidulus Montandon and A. pulchellus pallidulus Montandon are proposed as junior synonyms of A. pulchellus Montandon. Ambrysus pulchellus is newly recorded from Honduras, Nicaragua, and Panama in Central America. This species has the widest distribution in the subgenus Ambrysus Stål and includes parts of the Nearctic and Neotropical biogeographic realms. Ambrysus buenoi is distributed in Mexico and the United States, whereas A. californicus is endemic to the coastal ranges of California in the United States and A. vanduzeei to the Baja California Peninsula in Mexico.